IGLR-2, a Leucine-Rich Repeat Domain Containing Protein, Is Required for the Host Defense in Caenorhabditis elegans - Kuo, Cheng-Ju; Hsu, Ya-Chu; Wang, Sin-Tian; Liou, Bang-Yu; Lim, Serene Boon-Yuean; Chen, Yi-Wei; Chen, Chang-Shi (Frontiers in Immunology, 2020)
Enterohemorrhagic Escherichia coli (EHEC), a human pathogen, also infects Caenorhabditis elegans. We demonstrated previously that C. elegans activates the p38 MAPK innate immune pathway to defend against EHEC infection. However, whether a C. elegans pattern recognition receptor (PRR) exists to regulate this immune pathway remains unknown. PRRs identified in other metazoans contain several conserved domains, including the leucine-rich repeat (LRR). By screening a focused RNAi library, we identified the IGLR-2, containing the LRR domain, as a potential immune regulator in C. elegans. Our data showed that iglr-2 regulates the host susceptibility to EHEC infection. Moreover, iglr-2 is required for pathogen avoidance to EHEC. The iglr-2 overexpression strain, which was more resistant to EHEC originally, showed hypersusceptibility to EHEC upon knockdown of the p38 MAPK pathway. Together, our data suggested that iglr-2 plays an important role in C. elegans to defend EHEC by regulating pathogen-avoidance behavior and the p38 MAPK pathway.